Solve for p.

–3≤–69–p

11 answers

To solve the inequality \(-3 \leq -69 - p\), we can follow these steps:

  1. Start by isolating the term with \(p\). Add 69 to both sides:

    \[ -3 + 69 \leq -p \]

    This simplifies to:

    \[ 66 \leq -p \]

  2. To isolate \(p\), multiply both sides of the inequality by -1. Remember that when you multiply or divide by a negative number, you must reverse the inequality sign:

    \[ -66 \geq p \]

    or equivalently:

    \[ p \leq -66 \]

Thus, the solution is:

\[ p \leq -66 \]

Solve for t.
t–1+13≤15

To solve the inequality \( t - 1 + 13 \leq 15 \), follow these steps:

  1. Combine like terms on the left side:

    \[ t + 12 \leq 15 \]

  2. Next, isolate \( t \) by subtracting 12 from both sides:

    \[ t \leq 15 - 12 \]

    This simplifies to:

    \[ t \leq 3 \]

Thus, the solution is:

\[ t \leq 3 \]

that was wrong.

Let’s re-evaluate the inequality \( t - 1 + 13 \leq 15 \).

  1. Combine the constants on the left side: \[ t + 12 \leq 15 \]

  2. Now, isolate \( t \) by subtracting 12 from both sides: \[ t \leq 15 - 12 \]

    This simplifies to: \[ t \leq 3 \]

The solution remains \( t \leq 3 \). If there's a specific aspect you'd like me to address further or if you have a different interpretation of the problem, please let me know!

Solve for w.
2w+6≤9.78

To solve the inequality \(2w + 6 \leq 9.78\), follow these steps:

  1. Subtract 6 from both sides of the inequality:

    \[ 2w \leq 9.78 - 6 \]

    This simplifies to:

    \[ 2w \leq 3.78 \]

  2. Now, divide both sides by 2 to isolate \(w\):

    \[ w \leq \frac{3.78}{2} \]

    Simplifying that gives:

    \[ w \leq 1.89 \]

Thus, the solution is:

\[ w \leq 1.89 \]

Solve for k.
7–2k≥1

To solve the inequality \( 7 - 2k \geq 1 \), follow these steps:

  1. Start by isolating the term with \( k \). Subtract 7 from both sides of the inequality:

    \[ -2k \geq 1 - 7 \]

    This simplifies to:

    \[ -2k \geq -6 \]

  2. Next, divide both sides by -2. Remember that when you divide or multiply by a negative number, you must flip the inequality sign:

    \[ k \leq \frac{-6}{-2} \]

    This simplifies to:

    \[ k \leq 3 \]

Thus, the solution is:

\[ k \leq 3 \]

Solve for k.

2k–1≤3

To solve the inequality \(-2k - 1 \leq 3\), follow these steps:

  1. Start by isolating the term with \(k\). Add 1 to both sides of the inequality:

    \[ -2k \leq 3 + 1 \]

    This simplifies to:

    \[ -2k \leq 4 \]

  2. Next, divide both sides by -2. Remember that when you divide by a negative number, you must flip the inequality sign:

    \[ k \geq \frac{4}{-2} \]

    This simplifies to:

    \[ k \geq -2 \]

Thus, the solution is:

\[ k \geq -2 \]